Myeloid-derived suppressor cells and the efficacy of CD8(+) T-cell immunotherapy - Lesokhin, Alexander M. (Landes Bioscience, 2013)
Myeloid-derived suppressor cells (MDSCs) promote immune evasion, a key feature of oncogenesis. The restoration of immunosurveillance by immunomodulatory antibodies improves the survival of a subset of cancer patients. Preclinical studies suggest that the ablation of monocytic MDSCs may be a useful adjunct to available immunotherapeutic strategies against cancer.